Does Sticky Cost Behavior Affect Earnings Quality? Evidence From Egypt - Wahdan, Mohamed Aly; Ahmed, Ashraf Khalifa; Alsayed, Marwa Saber Hamoda (International Journal of Accounting and Financial Reporting, 2021)
This paper seeks to extend the literature on cost behavior by providing additional evidence on sticky cost behavior in developing countries namely Egypt. Moreover, it aims to determine to what extent sticky cost behavior affects earnings quality. The paper depends on a sample consists of 38 listed firms in the Egyptian Exchange over the period from 2004 to 2017. The findings reveal that total costs respond asymmetrically to the equivalent change in sales in six of the nine examined sectors. Furthermore, both patterns of sticky cost behavior, stickiness and anti-stickiness, negatively affect earnings quality. Therefore, managers, investors, and managerial accountants should take into account sticky cost behavior when making their decisions. This study contributes to the stream of research that integrates managerial accounting with financial accounting by combining sticky cost behavior with earnings quality. In addition, it extends the line of research related to the impacts of sticky cost behavior. Moreover, it gives new evidence on sticky cost behavior and its impacts from one of emerging countries.